2020
DOI: 10.1101/2020.03.12.989640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Angioplasty-induced epigenomic remodeling entails BRD4 and EZH2 hierarchical regulations

Abstract: Atherosclerosis is commonly treated with angioplasty which, however, evokes neointimal hyperplasia (IH) and recurrent stenotic diseases. Epigenomic investigation was lacking on postangioplasty IH. The histone acetylation reader BRD4 and H3K27me3 writer EZH2 are potent epigenetic factors; their relationship is little understood. Through genome-wide survey in the rat angioplasty model, we studied BRD4 and EZH2 functional regulations involved in IH.We performed chromatin immunoprecipitation sequencing (ChIPseq) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In the current study, as we sought to identify BRD4’s downstream functional mediators and CEBPD’s upstream epigenetic determinants in SMCs, the two searches converged. Using the information from chromatin immunoprecipitation and high-throughput sequencing (ChIP-seq) as a guide, 12 we observed that angioplasty injury induced enrichment of BRD4 and H3K27ac at the CEBPD gene. Indeed, BRD4 dominated CEBPD expression in SMCs.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, as we sought to identify BRD4’s downstream functional mediators and CEBPD’s upstream epigenetic determinants in SMCs, the two searches converged. Using the information from chromatin immunoprecipitation and high-throughput sequencing (ChIP-seq) as a guide, 12 we observed that angioplasty injury induced enrichment of BRD4 and H3K27ac at the CEBPD gene. Indeed, BRD4 dominated CEBPD expression in SMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Arteries were collected for ChIPseq at post-angioplasty day 7 as this is the peak time of pro-IH molecular and cellular events 14,15 . Epigenomic marks involved in transcriptional activation, including BRD4, H3K27ac, and H3K4me1 16 , were chosen for ChIP experiments, and the main body of data is available in our other report 17 . BRD4 and H3K27ac are associated with active enhancers, and H3K4me1 can be found with active, inactive, or poised enhancers.…”
Section: Angioplasty Injury Induces Brd4 and H3k27ac Enrichment At Thmentioning
confidence: 99%